Perancangan Ulang Tata Letak Fasilitas Pada Sistem Produksi Flow Shop (Studi Kasus Pt. Xxx Pekanbaru) - Tengku Nurainun; Arif Sulistyawan (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2016)
A production facility design in flow shop production systems without considering the process flow may cause an ineffective production process flow. The complexity increases if the distance among facilities is too far so it decreases the effectiveness and efficiency during the production activities. This research proposed a plant layout design that has considered the production flow. The plant layout design applied u-shape flow pattern. In this proposal layout design the number of machines were added depending on the machine requirements. The distance of material displacement before the improvement was 21.5 meters, while the total distance of the proposed design was 19 meters.Keywords: facility layout, flow shop production process, material flow